German Open : Gegenwartskunst in Deutschland. - Backhaus, Catrin; Berger, Doris; Birnbaum, Daniel; Brodbeck, Andrea; Bylow, Christina; Böhm, Simone; Dittmer, Peter; Dziewior, Yilmaz; Ebeling, Knut; Elben, Georg; Fleck, Robert; Frangenberg, Frank; et al. (Wolfsburg : Kunstmuseum Wolfsburg, 2000)
Pflumm, Daniel ; Dittmer, Peter ; Rehberger, Tobias ; Wohnseifer, Johannes ; Braun, Matti ; Meese, Jonathan ; Pernice, Manfred ; Hoderlein, Stefan ; Friedl, Peter ; Brandenburg, Marc ; Richter, Daniel ; Jankowski, Christian ; Althoff, Kai ; Mohr, Max ; Choi, Sunah ; Györfi, Alexander ; Mayer, Maix ; Flamm, Christian ; Specker, Heidi ; Schulz, Tilo ; Bonin, Cosima von ; Wagner, Silke ; Pommerer, Peter ; Rauch, Neo ; Majerus, Michel ; Eliasson, Olafur ; Hoischen, Christian ; Korpys, Andree & Markus Löffler ; Böhm, Simone ; Hess, Elmar ; Zehrer, Joseph ; Exler, Stefan ; Ackermann, Franz ; Kern, Stefan ; Schneider, Gregor ; Reinigungsgesellschaft ; Bock, John
biografie
German Open : Gegenwartskunst in Deutschland / Contemporary Art in Germany, Kunstmuseum Wolfsburg, 13. November 1999 - 26. März 2000
Duits & Engels
kunstcatalogus
Keywords: Duitsland